Naming Oneself in the Social Mirror: A Vignette-Based Survey - Valenzuela-Rabi, A (SAGE Publications Ltd, 2022)
In order to understand the way in which people self-identify in society and as a contribution to debates about class identity in Latin America, in this article the authors assess how individuals categorize themselves and others socially, and discuss whether a significant portion of the population classifies itself as middle class. They address the question of whether or not individuals’ representation of their social position is linked to social class, examining whether that position incorporates a socio-economic dimension, a hierarchical dimension, or even an element of moral value. The authors focus on how individuals name their own social position by means of a vignette-based survey applied in 2016 to a randomized sample of 2000 people in Chile. The results show that the theoretical notion of class is still of relevance to subjective positioning criteria, and that such criteria are specific to individuals who self-identify with lower or higher social positions. © The Author(s) 2020.